(untitled) (Heteroglossia – studia kulturoznawczo-filologiczne, 2017)
The present article describes stylistic peculiarities of advertising texts aimed at selling products. Many other linguistic means (phonetic, lexical, grammatical etc.) are of importance, but it is stylistic devices that make speech more expressive, picturesque and figurative. The words used in figurative meaning, which create images, are called stylistic figures. Owing to them (metaphors, personifications, similes, epithets, hyperboles, etc.) advertising language becomes more original and vivid and attracts consumers’ attention. The analysis is based on English and Russian advertisements of cosmetics. For buyers of cosmetics one of the most important aspects at choosing some product is its affect on gaining prestige with the aid of magnetic appearance and feeling of comfort. It is ensured by the use of one or another cosmetic product and expressed by linguistic stylistic means.